Who Was ʿUmar ibn Sayyid? A Critical Reevaluation of the Translations and Interpretations of the Life - Tamplin, William Costel (Journal of Arabic and Islamic Studies, 2017)
Recent criticism of the Life (1831) of ʿUmar ibn Sayyid has sought to overturn prior assumptions that ʿUmar was a Christian convert and a content slave to prove that ʿUmar was a crypto-Muslim and an aboli-tionist. This criticism posits the existence of esoteric “concealed utterances” available to the initiated reader throughout ʿUmar’s autobiography as evidence of his abiding Islam and opposition to slavery in general and his enslavement in particular. This paper reexamines the translations and interpretations of ʿUmar ibn Sayyid’s Life to demonstrate how little about him we can know given his poor command of classical Ara-bic, the second language in which he wrote his autobiography. Through a reexamination of ʿUmar’s auto-biography in light of 1) the political history of West Africa, 2) his relationship to classical Arabic and to language in general, and 3) a survey of the scholarship that verifiable mistranslations of his Life have gen-erated, I will demonstrate that ʿUmar’s poor command of Arabic makes drawing conclusions about his ideas about enslavement and Islam nearly impossible. Key words: Slave narrative, Arabic, translation, Islam, second language attrition, United States